Determination of the bioavailability and biodistribution of a single dose of oral cholecalciferol/Calcirol® soft gelatin capsule by pharmacoscintigraphy- CalSci study - Sahay, Rakesh; Saresa, Hiten; Changani, Mohit; Kotadia, Ravi; Soni, Ameet; Patel, Pratik; Khanna, Kushagra; Kumar, Neeraj; Gupta, Annie (International Journal of Basic & Clinical Pharmacology, 2023)
Background: It is required to study the bioavailability and biodistribution of specific cholecalciferol formulation before prescribing. Pharmacoscintigraphy is an established radiological-imaging technique that is used to map various drug formulations as they traverses the human body (biodistribution) in real-time. We evaluated the bioavailability and biodistribution pattern, transit time, and gastrointestinal clearance of a single dose of Calcirol® soft gelatin capsule 60,000 IU [an oral cholecalciferol (vitamin D) formulation] using pharmacoscintigraphy. Methods: Six male healthy adult volunteers were administered a single oral dose of Calcirol® soft gelatin capsule labelled with technetium-99m. Post-dosing, serial venous blood samples were collected till day 27 for the estimation of the plasma levels of 25-hydroxycholecalciferol and 1,25-dihydroxycholecalciferol levels. Different pharmacokinetic parameters were calculated. Sequential static gamma imaging was performed to evaluate the biodistribution of Calcirol® soft gelatin capsule. Descriptive statistics was used. Various pharmacokinetic parameters were calculated from the concentration-time curves. Statistical analysis was carried out using Student’s t-test. Suitable multivariate analysis was performed based on the distribution of data. All statistical analyses were performed using SAS® Software (v 9.4). Results: The overall absorption of Calcirol® soft gelatin capsule was 93.23%, which was fully from the small intestine. It led to achieving a sufficient level of 25-hydroxycholecalciferol (>60 ng/ml) within 6 hours of oral intake. The levels of plasma 25-hydroxycholecalciferol and 1,25-dihydroxycholecalciferol increased (maximum around 6 and 18 days, respectively). The small intestinal residence time was around 16 hours. No adverse event was noted. Conclusions: This was the first pharmacoscintigraphy study in the world which demonstrated the favourable bio-distribution of the Calcirol softgels supporting its role in vitamin D supplementation.